Implementation of the Fatigue Risk Management System Policy for Flight Safety at the Air Force Regional Command I (Resources, Procedures, and Compliance) - Mulyo Hadi; Izzatusholekha Izzatusholekha; Maya Puspita Dewi (Al-Makki Publisher, 2026)
Military aviation safety is a critical element in maintaining operational readiness and protecting national strategic assets. One of the most significant human factors affecting aviation safety is fatigue. In response, the Indonesian Air Force (TNI AU) has adopted the Fatigue Risk Management System (FRMS) as an integral part of its Safety Management System (SMS). This research aims to analyze the implementation of the FRMS policy for aviation safety at Air Force Regional Command I (Kodau I), focusing on the aspects of resources, procedures, and compliance. This research employs a qualitative descriptive approach using a case study method. Data were collected through field observations, in-depth interviews with key informants, and analysis of policy documents and safety reports. Data triangulation was applied to ensure the validity and reliability of the findings. The results indicate that in terms of resources, Kodau I has adequate physical facilities to support FRMS implementation; however, limitations remain in fatigue monitoring technology and the coverage of FRMS training programs. Regarding procedures, FRMS policies and standard operating procedures have been systematically developed and integrated into the SMS framework, yet data recording and processing systems remain largely manual, limiting long-term analytical capability. In terms of compliance, most personnel comply with flight duty time regulations, but challenges persist in fatigue reporting and training participation due to cultural factors